1998
DOI: 10.2466/pr0.1998.82.3.803
|View full text |Cite
|
Sign up to set email alerts
|

Relations of Autonomy, Self-Referenced Beliefs, and Self-Regulated Learning among Japanese Children

Abstract: This study was designed to investigate relations among autonomy, self-referenced beliefs, and self-regulated learning for 356 elementary school children (180 boys and 176 girls) from Grades 5 and 6. They were asked to complete a questionnaire designed to measure four types of motivation, self-esteem, strategy beliefs, capacity beliefs, control beliefs, and values, three types of goal orientations, and three types of learning strategies. Four types of motivation (external, introjected, identified, and intrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…We provide just a few examples. Yamauchi and Tanaka (1998) and Hayamizu (1997), in Japan, and Kim (2004), in South Korea, applied the SDT framework to assessments of autonomy in schoolchildren, finding that children who were lower in autonomy showed less motivation and interest, more superficial approaches to learning, and lower well-being. Chirkov, Ryan, Kim, and Kaplan (2003) asked people from four countries (Russia, United States, Turkey, and South Korea) to describe reasons why they would perform a variety of behaviors, including collectivistic and individualistic practices.…”
Section: Autonomy As a Cross-cultural Concept: Is It Only Western?mentioning
confidence: 99%
“…We provide just a few examples. Yamauchi and Tanaka (1998) and Hayamizu (1997), in Japan, and Kim (2004), in South Korea, applied the SDT framework to assessments of autonomy in schoolchildren, finding that children who were lower in autonomy showed less motivation and interest, more superficial approaches to learning, and lower well-being. Chirkov, Ryan, Kim, and Kaplan (2003) asked people from four countries (Russia, United States, Turkey, and South Korea) to describe reasons why they would perform a variety of behaviors, including collectivistic and individualistic practices.…”
Section: Autonomy As a Cross-cultural Concept: Is It Only Western?mentioning
confidence: 99%
“…Third, individuals of various ages, from babies (e.g., Warneken & Tomasello, 2008) to late adults (Kasser & Ryan, 1999), were found to benefit from greater autonomy. Fourth, the cross-cultural role of autonomy has perhaps received the greatest attention, with both single-country (e.g., Yamauchi & Tanaka, 1998) and multi-country (e.g., Chen, Van Assche, et al, 2015) studies indicating that autonomy satisfaction yields positive outcomes for individuals in nations with very different cultural backgrounds. Finally, most recently, individuals' personality traits were considered as potential moderators (Hagger, Koch, & Chatzisarantis, 2015;Mabbe, Soenens, Vansteenkiste, & Van Leeuwen, 2016).…”
Section: The Need For Autonomymentioning
confidence: 99%
“…Studies have shown that SDT is applicable in traditional collectivistic societies, for example, South Korea (Jang et al, 2009), Japan (Yamauchi and Tanaka, 1998), Turkey (Chirkov et al, 2003), and the Bedouin community (Kaplan et al, 2014). Recent studies have compared students from different cultural backgrounds and revealed that the psychological mechanism that links basic psychological needs and motivation is similar across cultures (Chen et al, 2015;Ginevra et al, 2015).…”
Section: Cultural Context and Teachers' Motivationmentioning
confidence: 99%